First Freshwater Bothriocephalidean (Cestoda) from Tropical South America, Closely Related to African Taxa - Scholz, Tomáš; Takemoto, Ricardo Massato; Kuchta, Roman (The Journal of parasitology, 2017)
Regobothrium microhamulinum n. gen. and n. sp. (Bothriocephalidea: Bothriocephalidae) is proposed to accommodate a new cestode from flatfish Catathyridium jenynsii (Chabanaud, 1922) (Pleuronectiformes: Acharidae; type host) and another 3 freshwater fishes of the orders Characiformes, Cyprinodontiformes, and Siluriformes in the Neotropical Region. The new genus is placed in the Bothriocephalidae because it possesses medioventral uterine and mediodorsal genital pores and a follicular vitellarium. Regobothrium n. gen. is characterized by possessing a tiny, slightly subovate scolex narrower than the strobila, with an apical disc armed with 2 semicircles of 15-17 tiny hooks in each and an acraspedote strobila. Regobothrium n. gen. differs from all bothriocephalid cestodes that have a scolex armed with hooks by their small size (maximum length less than 20 μm) and a triangular shape with the basal part (handle or basal plate) shorter than the distal coniform part (blade). In the other hooked bothriocephalids, hooks have a longer handle than a blade. Regobothrium microhamulinum n. gen. and n. sp. is the third bothriocephalidean cestode described from freshwater teleosts in South America but the first out of Patagonia. Molecular phylogenetics consider Regobothrium as a member of a lineage consisting of (up to now exclusively) freshwater bothriocephalids from the Ethiopian biogeographic region, thus indicating Gondwanan relationship.
Keywords: Cyprinodontiformes; Phylogeny; Brazílie; Cestoda; sladká voda; Jižní Amerika; Fish Diseases; zvířata; Tropical Climate; Catfishes; Ethiopia; Characiformes; sumci; platýsi; mikroskopie elektronová rastrovací; Flatfishes; Etiopie; nemoci ryb; Brazil; Animals; South America; fylogeneze; Microscopy, Electron, Scanning; tropické klima; Fresh Water